Metastatic unknown primary tumour presenting in pregnancy: a rarity posing an ethical dilemma. Issue 8 (30th July 2007) - Patni, Shalini; Wagstaff, John; Tofazzal, Nasima; Bonduelle, Myriam; Moselhi, Marsham; Kevelighan, Euan; Edwards, Steve
Abstract : This brief report raises the ethical dilemma encountered by an obstetrician involved in the care of a pregnant woman with life-threatening disease. This is a particularly difficult issue if the maternal well-being is in conflict with the survival of the unborn child.